La ortografía de Palma - Díaz Falconí, Julio (Mercurio Peruano, 2013)
Comparing the titles of Ricardo Palma’s Tradiciones written between 1851 and 1883 it can be established that the orthography used in the edition 1893-6 from Barcelona is better cared for than the 1883 Prince edition. Palma was not a reformer who systematically substituted /g/ for /j/. He could write the very title sometimes with /g/, and others with /j/; for instance, Un litijio original (the two words with /j/) and Un litijio [with j] original [with g].